Tinjauan Hukum Perlindungan Konsumen terhadap Kebijakan Penghapusan Kuota Pascabayar oleh Perusahaan Telekomunikasi di Indonesia - Muhd. Basry Hamaya (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The policy of postpaid data quota elimination by telecommunication companies in Indonesia has raised legal issues in the context of consumer protection. This practice is often implemented without transparency or explicit consent from consumers, despite the fact that the data quotas have been fully paid. This study aims to analyze the compatibility of the quota elimination policy with the principles of contractual fairness and consumer protection under Indonesian positive law. The research uses a normative juridical method, focusing on statutory regulations, legal doctrines, and comparative practices from other jurisdictions. The findings reveal that standard clauses regulating data quota forfeiture without a rollover or compensation mechanism contradict Article 18 of Law Number 8 of 1999 concerning Consumer Protection and violate the principles of good faith, balance, and transparency in contracts. Therefore, such policies are inconsistent with the doctrine of fair contracts and the legal responsibilities of business actors as mandated in the Indonesian consumer protection legal system. This study recommends the establishment of technical regulations by BRTI and the Ministry of Communication and Information (Kominfo) to ensure fair and sustainable protection of consumer rights over paid data services.